2008
DOI: 10.1534/genetics.107.084954
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Inbreeding From Pedigree Analysis of Purebred Dogs

Abstract: Dogs are of increasing interest as models for human diseases, and many canine population-association studies are beginning to emerge. The choice of breeds for such studies should be informed by a knowledge of factors such as inbreeding, genetic diversity, and population structure, which are likely to depend on breedspecific selective breeding patterns. To address the lack of such studies we have exploited one of the world's most extensive resources for canine population-genetics studies: the United Kingdom (UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
127
5
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 29 publications
9
127
5
4
Order By: Relevance
“…Bernese Mountain Dogs (18) and Italian Greyhounds (22) vanished completely and many other breeds suffered significant bottlenecks (Table S1). Bolstering or recreating these breeds was accomplished by crossing numerous other breeds, a practice that obscured whatever genetic signatures of their early heritage that existed before the World Wars, and ultimately led to highly inbred modern populations (23). Interestingly, the recent genetic homogenization has occurred despite the increase in phenotypic disparity as breeders have simultaneously closed breeding lines and selected for extreme morphological traits (24).…”
Section: Resultsmentioning
confidence: 99%
“…Bernese Mountain Dogs (18) and Italian Greyhounds (22) vanished completely and many other breeds suffered significant bottlenecks (Table S1). Bolstering or recreating these breeds was accomplished by crossing numerous other breeds, a practice that obscured whatever genetic signatures of their early heritage that existed before the World Wars, and ultimately led to highly inbred modern populations (23). Interestingly, the recent genetic homogenization has occurred despite the increase in phenotypic disparity as breeders have simultaneously closed breeding lines and selected for extreme morphological traits (24).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, usually only one bitch from a litter is included in breeding (the average in German Hovawarts is 1.15). The one-litter kennels observed in many dog breeds (Leroy et al, 2007;Calboli et al, 2008;Mäki, 2010), which produce disproportionately low numbers of breeding bitches , could also play a role in the random loss of mtDNA haplotypes present in a population. A general rule of "one kennel-one breeding bitch" also facilitates the extinction of dam lines.…”
Section: Discussionmentioning
confidence: 99%
“…Mäki (2010), in her study on two breeds (Nova Scotia Retriever, Lancashire Heeler), proposed crosses with other breeds (NS) or with unregistered farm dogs (LS) to increase the genetic diversity of the breeds. Calboli et al (2008) suggested relaxing breed rules to permit controlled outcrossing. Unfortunately, the case of the Polish Hounds indicates basic problems with such improvement programmes.…”
Section: Discussionmentioning
confidence: 99%
“…These analyses have indicated a number of unfavourable occurrences in dog breeding, such as a high level of inbreeding, high disproportion in the breeding use of sires, a low number of breed founders and strong imbalance in their contributions to a gene pool, all of which might result in the negative effects observed in the deteriorating health condition of a given breed and negatively influence its long-term perspectives. One way of enriching a limited gene pool is to introduce dogs of other breeds or of unknown origin that are phenotypically similar to a given breed (Leroy et al, 2006;Calboli et al, 2008;Mäki, 2010). However, the effectiveness of introducing new alleles into the gene pool of the breed depends mainly on breeders' will to use such dogs in breeding.…”
mentioning
confidence: 99%